2007
DOI: 10.1038/sj.jid.5700670
|View full text |Cite
|
Sign up to set email alerts
|

Increased ICAM-1 Expression Causes Endothelial Cell Leakiness, Cytoskeletal Reorganization and Junctional Alterations

Abstract: Tumor necrosis factor (TNF)-induced ICAM-1 in endothelial cells (EC) promotes leukocyte adhesion. Here we report that ICAM-1 also effects EC barrier function. Control- or E-selectin-transduced human dermal microvascular EC (HDMEC) form a barrier to flux of proteins and to passage of current (measured as transendothelial electrical resistance or TEER). HDMEC transduced with ICAM-1 at levels comparable to that induced by TNF show reduced TEER, but do so without overtly changing their cell junctions, cell shape, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
94
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 58 publications
6
94
0
2
Order By: Relevance
“…In addition, this cellular event is coupled with the increased adhesion of circulating leukocytes to the EC luminal surface (Clark et al, 2007). In the current study, the finding that cells which express high levels of ICAM-1 (IC1 hi-C ) reveal an increased EC contraction and junctional alteration (Figure 2A and B) also corroborates the pervious reports by others (Muller, 2001(Muller, , 2003.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…In addition, this cellular event is coupled with the increased adhesion of circulating leukocytes to the EC luminal surface (Clark et al, 2007). In the current study, the finding that cells which express high levels of ICAM-1 (IC1 hi-C ) reveal an increased EC contraction and junctional alteration (Figure 2A and B) also corroborates the pervious reports by others (Muller, 2001(Muller, , 2003.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies have demonstrated junctional alteration of ECs and inter-endothelial gap formation during diapedesis (McDonald et al, 1999;Johnson-Leger et al, 2000;Clark et al, 2007;Ley et al, 2007). However, we were particularly interested in whether contracted endothelium can be relaxed to recover its barrier function, because no report, to our knowledge, has directly addressed this question yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sICAM-1, which is derived from the proteolytic cleavage of membranebound ICAM-1, has been suggested in some biological contexts to have a role that is opposite to that of ICAM-1 (Clark et al, 2007). Interestingly, Sertoli cell barrier/BTB function was found to be compromised in vitro and in vivo following sICAM-1 overexpression, illustrating that sICAM-1 can negatively regulate Fig.…”
Section: Icam-1 In the Testis 5683mentioning
confidence: 99%
“…(46) Secondly, an increased incidence of thrombosi, (15) following cisplatin-based combination chemotherapy, including combinatorial therapies with antiangiogenic agents, (16) may at least in part be mediated by enhanced leukocyte/ endothelium interactions, since endothelial cells can be injured by the activation and the adhesion of neutrophil, the injury of the endothelial cells causes the exposure of subendothelial tissues, and then induces the platelet adhesion on these surfaces for the initial event of platelet aggregates. Thirdly, increased ICAM-1 expression can cause endothelial cell leakiness (47) which is also presented in our hamster's cheek pouch carcinoma tumor model. This may facilitate the high interstitial fluid pressure inside tumors and thus impede chemotherapeutic drug delivery.…”
Section: Discussionmentioning
confidence: 99%